Increasing Reading Literacy in Al-Barokah Islamic Boarding School Students in Sungai Asam Village through Gerakan Literasi Sekolah (GLS) - Julianto; Aulia Azimi; Hani Meilita Purnama Subardi; Wulan Wahyu Ningrum; Pratiwi Kurniati; Dini Lestary; Muhammad Tezar; Dewa Ruci; Nur Atiqah; Reni Helvira; Monica Olivia; Ari Widiati; Syamratun Nurjannah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Literacy is a person's ability to process and understand information when carrying out the process of reading and writing. Literacy has many types, such as reading and writing literacy, numeracy literacy, digital literacy, scientific literacy, financial literacy, and cultural literacy, and several other forms of literacy. Literacy refers to competencies or abilities that are more than just the ability to read and write. Through this PKM activity carried out by lecturers in Sungai Asam Village regarding literacy to build the Village Economy in Sungai Asam Village, lecturers can express and convey ideas in helping children, students, and the surrounding community to provide an understanding of the importance of education and literacy in increasing community expertise in managing Natural Resources in Sungai Asam Village which has the potential to improve the economy of the surrounding community. The Lecturer PKM activity was attended by lecturers, IAIN Pontianak students, the surrounding community including students from the Al-Barokah Islamic Boarding School in Sungai Asam Village.